Sexual suggestiveness in Madonna's music videos (1982-2012) - Conlu, Jeffrey G.; Duarte, Yevgeny Marie C. (2013.)
In order to promote publicity, artists portray themselves in varying images corresponding to the theme they?re trying to convey in their music videos. One prevalent subject depicted in this medium is sexual suggestiveness. The purpose of this study was to perform a content analysis to measure sexual suggestiveness in the music videos of Madonna as she is the artist most associated with the said theme. It was found out in the results that majority of the sixty-seven music videos are sexually suggestive. Because Madonna more often than not played the role of sex object, she obtained this mark or branding and made her very controversial. Also through her music videos, Madonna created a new wave for women influencing them to be powerful and independent. This study then highlights the responsibility of the artist as well as the music video industry to present positive attitudes on sexual behaviour.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Music Video -- Madonna -- 1982-2012.